Transforming Energy Efficiency Markets in Developing Countries : The Emerging Possibilities of Super ESCOs - Sarkar, Ashok; Moin, Sarah (World Bank, Washington, DC, 2018)
Over the past decade, Super ESCOs have emerged as a viable alternative to private sector ESCOs. These government established entities are well positioned to address market barriers and realize energy efficiency potential of the public sector even as they facilitate the development of private sector ESCOs. The concept, structure, and functions of Super ESCOs are still evolving, but experience to date has shown that Super ESCOs can unlock energy efficiency markets facing challenges with financing, delivery, and implementation.